Expressão de leptina e receptor de leptina (obr) como fator de risco para neoplasias de mama em cadelas e correlação com a obesidade - Blanca, William Torres (2017)
In humans and bitches obesity is considered a risk factor in the development of breast câncer. Leptin is a hormone synthetized by adipocytes that stimulates the proliferation of cancer cells. The high prevalence of obesity and breast tumors in bitches, studies aiming at a better understanding of the role of leptin in canine obesity, as well as its correlation with breast tumors, are of the utmost importance. A review of the literature on canine obesity, the relationship between obesity and mammary carcinomas, and the relation between obesity and the imunohistochemical marking of leptin and its receptor were carried out. The objective of this study was to verify the expression of leptin and its receptor in mammary carcinomas of bitches by means of the immunohistochemical technique and to correlate this expression with obesity, tumor size, age, type and histological grade. Obesity was also related to tumor size, age and histological grade. We used 84 bitches, submitted to surgical excision of mammary carcinomas, totaling 95 samples of simple and complex carcinomas that were submitted to immunohistochemical evaluation for the expression of leptin and its receptor. Complex carcinomas corresponded to 41% of the samples (39/95) and 59% simple carcinomas (56/95). The body mass index of dogs (BMI), 9.52% were underweight (8/84), 29.76% were within ideal weight (25/84), 33.33% were overweight (28/84) and 27.39% were obese (23/84) at the time of mastectomy. It was observed that the age of the obese animals with mammary carcinomas was smaller and that obese animals were carriers of tumors with larger sizes when compared to those with other classifications of body conditions. The expression of leptin was not directly related to the BMI, but the expression of ObR was higher (p <0.05) in bitches with higher BMI values. There was a correlation between age and leptin expression indicating that older animals are express leptin more frequently. Obesity may be considered a risk factor for breast carcinomas in bitches, once with obese female dogs present early breast carcinomas and tumor masses of larger size. Moreover, the expression of Obr is greater in carcinomas of obese bitches.